Allocation of attention and the delayed reaction of stock returns to liquidity shock: Global evidence - Lee, Kuan Hui; Wang, Shu Feng (Journal of Empirical Finance, 2023)
For 57,000 stocks from 40 countries during 1985–2020, we find significant delay in the response of stock returns to liquidity shock. Our measure of delay is larger in countries with good informational environments even after controlling for institutional frictions such as market illiquidity, stock market development, and short-sale constraint. The delay is reduced in large down markets, but not in large up markets. Our findings imply that investor inattention is an important source of price delay and that attention allocation is affected by a country's informational environment: In countries where an ample amount of information is available, investors allocate disproportionately less attention to elusive and non-salient events such as stock liquidity shock. Overall, our findings suggest that high informational quality at the country-level may work as a friction in the presence of investor inattention.
Keywords: Attention; Delay; International stock market; Liquidity; Predictability; Transparency; Underreaction